Pelatihan Manajemen Sampah Organik dan Non-Organik di SDN 3 Tumbang Tahai Kota Palangka Raya - Nugroho, Wahyu; Putra, Kharisma Nugraha; Samudra, Agung; Wagati, Fitria; Arantika, Jane; Fitriani, Desy; Adelia, Siska; Wahyuningsih, Teresya (Jurusan Pendidikan Ilmu Pengetahuan Sosial, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2025)
This community service activity aims to enhance the knowledge and skills of students and teachers at SDN 3 Tumbang Tahai, Palangka Raya City, in managing organic and non-organic waste. The activity was carried out on August 7, 2025, through several stages, namely preparation, counseling, demonstration, hands-on practice, mentoring, and evaluation. The counseling method was used to provide conceptual understanding regarding types of waste and their environmental impacts, while demonstrations and practical activities on waste sorting and processing organic waste into compost were conducted to instill applicable skills in the participants. The results show that participants were able to identify the differences between organic and non-organic waste, practice proper waste sorting, and understand the basic composting process. Teachers also gained new insights that have the potential to be integrated into learning activities and environmentally friendly school programs. Overall, this activity contributed positively to fostering environmentally conscious behavior in the school and supported efforts to create a clean, healthy, and sustainable learning environment.